1990
DOI: 10.3109/02688699008992763
|View full text |Cite
|
Sign up to set email alerts
|

Computerized tomographic stereotaxy in the management of 200 consecutive intracranial mass lesions. Analysis of indications, benefits and outcome

Abstract: Two hundred consecutive stereotactic procedures were performed. These were 153 biopsies and 43 therapeutic procedures. The latter included aspiration of craniopharyngiomata, arachnoid cysts, deep-seated abscesses, and the destruction of colloid cysts. Cryogenesis was used to treat an arteriovenious malformation (AVM) in one case. In four cases, the system was used to locate lesions during open surgery. Leksell stereotactic systems were used throughout. The ages of the patients ranged between 12 months and 83 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 14 publications
1
14
0
1
Order By: Relevance
“…In functional neurosurgery, the coordinates of the exact target point are calculated from preoperative CT scans where the skull is closed and, during physiological conditions, the brain is floating in the cerebrospinal fluid (CSF). During thalamotomy in many centres, an incision is made using an open surgical procedure with the patient in a sitting position [7,[20][21][22]. Some stereotaxic neurosurgeons have observed that such a procedure in the sitting position influenced the location of the brain relative to the skull during the functional stereotaxic thalamotomy procedure after the skull had been opened [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…In functional neurosurgery, the coordinates of the exact target point are calculated from preoperative CT scans where the skull is closed and, during physiological conditions, the brain is floating in the cerebrospinal fluid (CSF). During thalamotomy in many centres, an incision is made using an open surgical procedure with the patient in a sitting position [7,[20][21][22]. Some stereotaxic neurosurgeons have observed that such a procedure in the sitting position influenced the location of the brain relative to the skull during the functional stereotaxic thalamotomy procedure after the skull had been opened [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…However, in some patients biopsy is precarious or not feasible due to size or location of the lesion, cerebral edema, concomitant disease, or lack of patient's consent. Moreover, a conclusive histologic diagnosis cannot be achieved in up to 10% of biopsies (Bernays et al, 2002;Hall, 1998;Wild et al, 1990). A probable diagnosis must then be made on clinical, radiologic, and biochemical/serologic findings in this situation.…”
mentioning
confidence: 97%
“…Several authors have recorded the utility of stereotactic techniques in the management of brain abscesses. 6,11,25,34,38,43,47,53,55,61,62 There are several advantages of stereotactic aspiration. Only stereotactic aspiration is appropriate for small, deepseated abscesses or those located in eloquent regions of the brain, because it provides a direct and rapid access to the abscess through a predetermined route.…”
Section: Role Of Stereotaxy In Management Of Brain Abscessmentioning
confidence: 99%